Unilateral posterior cervical spinal cord infarction due to spontaneous vertebral artery dissection. (March 2014) - Richard, Sébastien; Abdallah, Chifaou; Chanson, Anne; Foscolo, Sylvain; Baillot, Pierre-Alexandre; Ducrocq, Xavier
<x content-type="archive" xml:space="preserve">Abstract</x> Context Ischemia of the cervical spinal cord is a rare complication of spontaneous vertebral artery dissection (VAD) and usually involves the ventral portion. We describe a less evocative clinical presentation and images of unilateral posterior spinal cord infarction due to spontaneous VAD in order to facilitate early diagnosis. Findings A previously fit 30-year-old man presented with persistent headaches and proximal motor deficit of the right arm. He was diagnosed with spontaneous dissection of both vertebral arteries, with occlusion of the right one, and the right carotid artery. Neurological examination also revealed a right C2–C3 tactile sensory loss, with unilateral proprioceptive deficit below. Brain images revealed small bilateral cerebellar infarcts which could not be responsible for the clinical symptoms. Magnetic resonance imaging of the spinal cord showed a right posterior cervical spinal cord infarction. The patient achieved nearly complete recovery after several weeks of anticoagulation and rehabilitation. Conclusion and clinical relevance Infarction of the caudal portion of the cervical spinal cord, especially unilateral, caused by spontaneous VAD, has rarely been described and is certainly under-diagnosed due to less suggestive symptoms, like unilateral and mainly sensory deficit. Nevertheless, early diagnosis of this condition is important to guide patient management and rehabilitation.